Piezoelectric material with perovskite structure for high working temperature and manufacturing method thereof

By providing a compound with a perovskite structure, the existing piezoelectric materials have limited temperature range and difficulty in accuracy in manufacturing process are solved, and materials with excellent piezoelectric functions at high temperatures are realized, and production efficiency and environmental protection are improved.

CN119768381APending Publication Date: 2025-04-04PI CERAMIC GMBH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380049172.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-23
Filing Date
2023-05-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The use temperature range of existing piezoelectric materials such as PZT is limited at high temperatures, and the hygroscopicity and high water solubility of potassium compounds lead to difficulties in accurate weighing and mixing during the manufacturing process, affecting product quality and repeatability.

Method used

A compound having a perovskite structure is provided, with a base composition of AgxBiyMzFevNwO3, wherein x+y+z and v+w are both in the range of 0.9 to 1.1, M is selected from Pb and/or Ba, and N is selected from Ti and/or Zr. The compound has low water solubility and hygroscopicity, is easy to handle, and can exhibit excellent piezoelectric functions at high temperatures.

Benefits of technology

Materials with excellent piezoelectric functions at high temperatures are realized, while simplifying the process and reducing the use of organic solvents, the quality and production efficiency of the material are improved and the environmental impact is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203389730000101
    Figure BDA0005203389730000101
  • Figure BDA0005203389730000111
    Figure BDA0005203389730000111
  • Figure BDA0005203389730000121
    Figure BDA0005203389730000121
Patent Text Reader

Abstract

The invention relates to a compound having a perovskite structure, the basic composition of which is AgxBiyMzFevNwO3, where x + y + z = 0.9 to 1.1 and v + w = 0.9 to 1.1, where M is selected from Pb and / or Ba and where N is selected from Ti and / or Zr, and which can be used as a basis for producing perovskite materials and functional ceramics having piezoelectric properties at high temperatures. Furthermore, a method for producing a material having a piezoelectric function is described, which ensures consistent and high product quality while providing advantages in terms of safety and can be produced without the use of organic solvents. Furthermore, a piezoelectric device comprising the above perovskite material or the compound having a perovskite structure is described.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition having a perovskite structure, which can be used as a starting material for manufacturing perovskite functional ceramics having piezoelectric properties at high temperatures.

[0002] Furthermore, methods of manufacturing a material comprising a given composition and a piezoelectric device comprising the material are described. Background Art

[0003] Piezoelectric materials have the property that their electrical polarization changes as a result of mechanical action (piezoelectric effect) or that the application of a voltage leads to a change in the material's dimensions or its mechanical movement (inverse piezoelectric effect). Due to these functions, piezoelectric elements are used as sensors and actuators in many technical fields, for example in medical technology, sonar applications, ultrasound technology, consumer electronics, mechanical engineering, the automotive industry and aerospace.

[0004] A wide variety of materials suitable as a basis for piezoelectrically active components are described in the prior art.

[0005] For example, DE 10 2019 135 245 B9 discloses a piezoelectric composition comprising silver and an oxide, wherein the oxide has a perovskite structure and is at least partially composed of the formula x[Bi m FeO3]-y[Ba n TiO3] indicated.

[0006] The most common piezoelectric material today is based on the ferroelectric crystal lead zirconate titanate (Zr x Ti (1-x) )O3 (PZT), which, like its cousin barium titanate, usually has a perovskite structure. Perovskite refers to a general type of tightly packed ionic structure ABX3, where A and B are cations and X is an anion. By distorting the perovskite structure, polarization can be induced in the lattice, leading to dipole formation, which is the root cause of the piezoelectric properties of many perovskites. For example, in lead zirconate titanate (PZT), the piezoelectric properties of the perovskite are induced at the Curie temperature (T c ) below, the titanium ions shift from their central positions in the ionic lattice, forming a dipole lattice with piezoelectric properties.

[0007] However, the operating temperature range of PZT is very limited. In this case, PZT can be used continuously and maintain a sufficient piezoelectric coefficient of more than 50pC / N (under the condition of electric field and length change along the polarization axis direction (longitudinal effect)). 33 The maximum temperature is typically about 250°C.

[0008] To solve this problem, WO 2019 / 243778 A1, US 2013 / 0207020 A1 and US 2018 / 0315916 A1 describe materials with improved piezoelectric function at high temperatures, wherein perovskite materials (Bi a K 1-a )TiO 3- y BiFeO3-PbTiO3 (or other chemical formulas expressed as K x Bi y Pb z Fe v Ti w O3, where x+y+z=1.0 and v+w=1.0) as the material basis.

[0009] For manufacturing (Bi a K 1-a )TiO 3-y BiFeO3-PbTiO3, in WO 2019 / 243778 A1, US 2013 / 0207020A1 and US2018 / 0315916 A1, in addition to Bi2O3, Fe2O3 and TiO2, PbO as a lead component and K2CO3 as a potassium component must also be weighed and mixed.

[0010] Potassium carbonate (K2CO3) is highly hygroscopic and has a water solubility of L = 1120 g / l at 25°C, while other potassium compounds are also generally hygroscopic and water-soluble (e.g. KOH: L = 1130 g / l; KNO3: L = 316 g / l; K2C2O4: L = 360 g / l; K2CO3: L = 1120 g / l; KCl: L = 347 g / l, all at 25°C). These properties pose great challenges to the manufacturing process of piezoelectric ceramic materials in the following aspects:

[0011] The significant hygroscopicity of potassium compounds results in constant absorption of moisture and makes it difficult to accurately and consistently weigh the amounts of reactants, which affects, among other things, product quality and the reproducibility of the manufacturing process unless controlled environmental conditions are ensured at considerable cost and effort.

[0012] Furthermore, the high water solubility of potassium compounds requires mixing in organic, liquid, anhydrous media. The corresponding solvents, such as the isopropanol used in US2013 / 0207020 A1 and US2018 / 0315916 A1, are flammable. Especially in the context of the "scale-up" manufacturing process, complex safety precautions are therefore required. In any case, it is desirable, especially for environmental reasons, to reduce the use of organic solvents in the manufacturing process to a minimum.

[0013] Publication EP 3 331 840 A1 describes a method in which the starting materials are homogenized in an aqueous suspension and then spray-frozen granulated in order to prevent water-soluble components, such as alkalis, from dissolving out during subsequent processing and separating during drying. However, in addition to requiring additional process steps, this method does not minimize the errors in weighing the starting materials.

[0014] WO 2019 / 243778 A1 describes dry mixing without the use of a liquid medium. However, this method has considerable disadvantages, since the hygroscopic properties of the potassium compounds can lead to agglomerations during the feeding and actual dry mixing, resulting in disadvantageously uneven mixing distributions, which can reduce the quality of the material obtained.

[0015] Therefore, in view of the above, an object of the present invention is to provide a compound and a material which are characterized by excellent piezoelectric functionality at high temperatures and which can be provided in high quality and high yield by a simple, economical and environmentally friendly method. Summary of the invention

[0016] Therefore, as a solution to the above problems, the present invention provides a compound having a perovskite structure, characterized in that it has a basic composition of Ag x Bi y M z Fe v N w O3, wherein x+y+z=0.9 to 1.1 and v+w=0.9 to 1.1, wherein M is selected from Pb and / or Ba, and wherein N is selected from Ti and / or Zr.

[0017] In addition, a material with piezoelectric function is also provided, characterized in that it includes a perovskite material containing the above compound.

[0018] The present invention also provides a method for producing the above-mentioned material having piezoelectric function.

[0019] Furthermore, a piezoelectric device is described, which preferably comprises a piezoelectric ceramic body having at least two electrodes, the piezoelectric device comprising the above-mentioned compound having a perovskite structure or the above-mentioned material having a piezoelectric function.

[0020] Advantageous embodiments of the invention can be gathered from the dependent claims and from the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention will be described in more detail with reference to the accompanying drawings, wherein:

[0022] Figure 1 An exemplary process for manufacturing a piezoelectric ceramic material according to the present invention is shown, and

[0023] Figures 2A and 2B show the ceramic images of an exemplary sintered composition. Detailed Description

[0024] The present invention and its advantages will be described in more detail below based on preferred embodiments.

[0025] In one embodiment, the present invention relates to a compound having a perovskite structure, characterized in that the compound has a basic composition Ag x Bi y M z Fe v N w O3, where x + y + z = 0.9 to 1.1 and v + w = 0.9 to 1.1, where M is selected from Pb and / or Ba, preferably Pb or Ba, and where N is selected from Ti and / or Zr, preferably Ti or Zr.

[0026] In a preferred embodiment, M contains both Pb and Ba such that the compound has a basic composition Ag x Bi y (Pb,Ba) z Fe v N w O3, and z is the mass fraction of the sum of the two metals in the basic composition.

[0027] In a further preferred embodiment, M represents Pb such that the compound has a basic composition Ag x Bi y Pb z Fe v N w O3.

[0028] Preferably, the sum of x, y, and z is 0.95 to 1.05, and the sum of v and w = 0.95 to 1.05. Particularly preferably, x + y + z = 1 and v + w = 1. Generally, x, y, z, v, and w independently satisfy 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < v < 1, and 0 < w < 1.

[0029] It has been found that silver compounds are characterized by relatively low water solubility and non-hygroscopic properties, which, in addition to being easy to handle, can also be used to manufacture materials with excellent piezoelectric properties at high temperatures.

[0030] In a preferred embodiment, x, y, z, v, and w satisfy:

[0031] 0.005 ≤ x ≤ 0.30

[0032] 0.40 ≤ y ≤ 0.90

[0033] 0.01≤z≤0.70

[0034] 0.40≤v≤0.80

[0035] 0.20≤w≤0.60.

[0036] In a further preferred embodiment, x, y, z, v and w satisfy:

[0037] 0.01≤x≤0.20

[0038] 0.50≤y≤0.80

[0039] 0.05≤z≤0.50

[0040] 0.50≤v≤0.70

[0041] 0.30≤w≤0.50.

[0042] In a particularly preferred embodiment, the piezoelectric properties in the high temperature range (e.g., as determined by T c and d 33 Determined), x, y, z, v and w satisfy:

[0043] 0.02≤x≤0.14

[0044] 0.56≤y≤0.76

[0045] 0.10≤z≤0.42

[0046] 0.54≤v≤0.62

[0047] 0.38≤w≤0.46.

[0048] Perovskites are characterized by a general structural type of tightly packed ionic structures ABX3, wherein A and B represent cations and X represents anions. In this regard, it is preferred that in the compounds according to the invention, Ag and Bi (or Ag + and Bi 3+ ) occupies position A in the underlying perovskite base structure ABO3. Additionally or alternatively, preferably in the compounds according to the invention, Fe and Ti or Zr (or Fe 3+ and Ti 4+ or Zr 4+ ) occupies position B in the underlying perovskite infrastructure ABO3.

[0049] Typically, the compounds according to the invention have an orthorhombic / rhombohedral crystal structure.

[0050] The lower tolerance limit of the ionic radius that forms the perovskite structure is defined by the Goldschmidt tolerance factor t (see VM Goldschmidt: Die Gesetze der Krystallochemie. In: Die Naturwissenschaften, Vol. 14, No. 21, 1926, pp. 477-485). This also enables the degree of distortion to be estimated and conclusions about the key length ratio to be drawn. The compounds according to the invention preferably have a perovskite structure tolerance factor according to Goldschmidt t in the range of 0.820 to 0.880, more preferably in the range of 0.840 to 0.860. In order to calculate the Goldschmidt tolerance factor t according to the invention, the effective ionic radius according to RD Shannon is used; "Revised Effective Ionic Radii and Systematic Studies of Interatomic Distances in Halides and Chalcogenides"; Acta Crystallography; A32; 1976; 751-767.

[0051] In another embodiment, the present invention provides a material with piezoelectric function, characterized in that the material includes a perovskite material, and the perovskite material contains the above-mentioned compound with a perovskite structure.

[0052] Preferably, the total amount of non-perovskite phase present in the material is less than 10 wt %, particularly preferably less than 8 wt %, more preferably less than 5 wt %, even more preferably less than 2 wt %, even more preferably less than 1 wt %, most preferably less than 0.1 wt %. The amount of non-perovskite phase present in the ceramic may be trace amounts.

[0053] It is particularly preferred here that the material consists of a perovskite material which is pure in terms of X-ray imaging and contains no non-perovskite foreign phases which are detectable in terms of X-ray imaging.

[0054] The perovskite material contains Ag as the basic component. x Bi y M z Fe v N w O3 (wherein x+y+z=0.9 to 1.1 and v+w=0.9 to 1.1), may also contain one or more perovskite phases. Other perovskite phases may have a rhombohedral or tetragonal crystal structure. Preferably, the perovskite material does not contain a phase having the formula (Bi a K 1-a)TiO3 (wherein 0.4≤a≤0.6) perovskite phase. In a further preferred embodiment, the perovskite material does not contain potassium ions.

[0055] In the perovskite material included in the material, one or more of Ag, Bi, M, Fe and N may be substituted by a dopant, for example, to induce a change in Curie temperature and / or piezoelectric activity.

[0056] The dopant may be added in a suitable amount, for example, in an amount of up to 2 wt%, preferably up to 1 wt%, in an embodiment up to 50 atomic % or up to 20 atomic %. Further preferably, the dopant is added in an amount of at least 0.001 wt%, more preferably at least 0.005 wt%. The information shown in wt% refers to the total weight of the perovskite material.

[0057] Preferred dopants are metal dopants.

[0058] In this case, the metal dopant can act as a substitute for the A position in the underlying perovskite infrastructure ABO3 and replace, for example, Ag and / or Bi. Preferably, the metal dopant at the A position is selected from the group consisting of Li, Na, Ca, Sr, Ba and rare earth metals. Doping Li, Na, Ca, Sr or Ba at the A position can reduce dielectric loss, change (e.g., increase) the Curie point and / or favorably affect the phase composition, while substitution with rare earth metals (e.g., La or Nd) can improve piezoelectric activity.

[0059] The metal dopant may be a metal dopant for the B site in the underlying perovskite infrastructure ABO3 and may replace, for example, Fe and / or Ti.

[0060] Preferred dopants at the B position may be selected from the group consisting of, for example, Ti, Zr, W, Nb, V, Ta, Mo and Mn. Preferred metal dopants at the B position may have a higher valence than the valence of the metal being replaced, thereby increasing the specific resistance of the material and reducing its conductivity. In a further preferred embodiment, with respect to improving insulation resistance and reducing dielectric losses, the metal dopant at the B position is Mn.

[0061] As mentioned above, the material according to the invention features an advantageous piezoelectric function in the high temperature range, ie operating temperatures above 250° C. and typically up to at least 500° C.

[0062] Preferably, the material according to the invention has a piezoelectric constant d 33 (under electric field and length change in the direction of the polarization axis (longitudinal effect)) greater than 50 pC / N, further preferably greater than 60 pC / N and particularly preferably greater than 70 pC / N, all determined in accordance with EN 50324. Piezoelectric constant d 33Typically it is 50 pC / N to 110 pC / N, for example 60 to 100 pC / N.

[0063] Furthermore, the material is preferably suitable for long-term use at a maximum operating temperature of at least 450°C, more preferably at least 500°C, particularly preferably at least 550°C.

[0064] Curie temperature T of functional ceramics c It can be determined according to EN 50324 and is preferably at least 500°C, more preferably 550°C to 640°C.

[0065] The dielectric constant ε is defined as the ratio of the absolute dielectric constant of the material to the dielectric constant of vacuum (ε0 = 8.85 × 10 -12 F / m), preferably 100 to 500, such as 180 to 340.

[0066] The dielectric loss factor tan δ of the material can be determined by small signal measurement and is preferably 0.05 or less, more preferably 0.04 or less, for example 0.01 to 0.03.

[0067] The present invention also relates to a method for manufacturing the above-mentioned material having piezoelectric function, which comprises:

[0068] (1) mixing a raw material combination comprising Ag, Bi, Pb and / or Ba, Fe, Ti and O, and optionally grinding the raw material combination;

[0069] (2) heat treating the mixed and optionally ground raw material combination to provide a raw material having a basic composition of Ag x Bi y M z Fe v Ti w O3 perovskite material, wherein x+y+z=0.9 to 1.1 and v+w=0.9 to 1.1,

[0070] wherein M is selected from Pb and / or Ba.

[0071] In a preferred embodiment, the raw material combination comprises Ag, Bi, Pb, Ba, Fe, Ti and O, so that M in the basic composition comprises Pb and Ba. In a further preferred embodiment, M represents only Pb.

[0072] The manufacturing method according to the present invention may include, for example, Figure 1 Additional method steps are shown.

[0073] In general, the method starts from providing raw materials (optionally with dopants) and weighing them. The starting raw materials are not particularly limited and can be especially oxides, carbonates, hydroxides, halides or other salts of metals used. Preferably, the raw material combination includes Bi2O3, Fe2O3, TiO2 and PbTiO3 and / or BaTiO3, and one or more compounds selected from Ag2O, AgF, AgCl, AgBr, AgI, AgNO3, AgCNO, AgN3, Ag2S and AgOH. In view of the favorable low water solubility of each raw material, the raw material combination includes Bi2O3, Fe2O3, TiO2 and PbTiO3 and / or BaTiO3, and one or more compounds selected from Ag2O, AgCl, AgBr, AgI, AgCNO, AgN3, Ag2S and AgOH. In a particularly preferred embodiment, Ag2O is used as the silver-containing raw material (solubility L=0.025 g / l in water at 25°C). Other raw materials (e.g. metal oxides such as WO3 or MoO3) may be added as required, as long as they do not hinder the formation of a silver-containing raw material having the composition Ag2O. x Bi y M z Fe v N w Perovskite structure of O3, where x+y+z=0.9 to 1.1 and v+w=0.9 to 1.1.

[0074] Compared to known methods which rely on the use of raw materials with significant hygroscopicity (e.g. potassium compounds), the method according to the invention enables simple, constant and precise weighing of the raw materials and does not require any additional measures (e.g. pre-drying and / or weighing in a protective gas atmosphere).

[0075] The raw material combination is then mixed and optionally ground in a dry state or in a liquid medium, wherein an aqueous medium (e.g. water) can advantageously be used as the liquid mixing and / or grinding medium. By minimizing or eliminating the use of organic solvents, the environmental friendliness of the process can be improved, especially when scaling up the production process, and the requirements for work and laboratory safety can be reduced without affecting product quality and consistency.

[0076] The mixed and optionally ground raw material combination is calcined to provide a raw material having a composition of Ag. x Bi y M z Fe v N wPerovskite material of O3, wherein x+y+z=0.9 to 1.1 and v+w=0.9 to 1.1, wherein M is selected from Pb and / or Ba and wherein N is selected from Ti and / or Zr. It is worth noting that calcination can be carried out before or after grinding, and further coarse grinding and fine grinding steps can be inserted. The calcination conditions are not particularly limited and can be set in an appropriate manner by those skilled in the art. Calcination is generally carried out at a temperature of greater than 600°C to about 900°C.

[0077] The subsequent further processing of the obtained calcined product can be carried out according to known methods.

[0078] For example, the calcined material can be slurried in a liquid (preferably aqueous) medium and cast into a foil, which can then be subjected to a multilayer process (e.g., including printing, stacking, laminating and / or separating) before the material is sintered. Alternatively, the calcined material can be subjected to a "co-firing" process, in which the foils are provided with electrodes in the green state, laminated to form a piezoelectric element, and then sintered together with the internal electrodes in a single process step, as described, for example, in DE 10234787C1. Another processing possibility is to slurry the calcined material in a liquid (preferably aqueous) medium, or to plasticize and homogenize it with a suitable binder, and then process it by spraying granulation and subsequent press molding before sintering the molded material. Alternatively, the calcined material can also be finely ground and then granulated and press molded (e.g., according to Figure 1 shown).

[0079] The sintering conditions are not particularly limited and can be selected in an appropriate manner by a person skilled in the art. The sintering is usually carried out at a temperature of at least 850° C., preferably 950° C. or higher.

[0080] The sintered material can be mechanically processed (including, for example, grinding and / or cutting), contacted, polarized (for example, applying a DC electric field of about 2 to 10 kV / mm at a temperature of 20 to 150° C.), and electrically measured according to known methods to provide a piezoelectric ceramic material.

[0081] Another embodiment of the present invention relates to a piezoelectric device, which includes the above-mentioned compound having a perovskite structure or the above-mentioned material having a piezoelectric function.

[0082] The piezoelectric device may be a piezoelectric actuator, a sensor or a transformer.

[0083] Typically, the piezoelectric device includes the compound having a perovskite structure according to the present invention or the material having a piezoelectric function according to the present invention in a piezoelectric ceramic body, and at least two electrodes.

[0084] The piezoelectric ceramic body can be designed as a shaped body (usually by mechanical hydraulic pressing), for example in the form of a disk, plate, rod, hemisphere or ring.

[0085] The piezoelectric material and / or the electrode may be formed into a stacked layer structure. The stacked piezoelectric device may have a plurality of internal electrode layers and a plurality of piezoelectric layers, wherein each electrode layer is alternately stacked or layered with a corresponding piezoelectric layer, wherein at least one of the plurality of piezoelectric layers comprises a compound having a perovskite structure according to the present invention or a material having a piezoelectric function according to the present invention. In addition, the structure stacked in this manner may include additional layers as required, such as one or more buffer layers, a substrate layer, a conductive portion, and / or an insulating layer. The thickness and area of ​​the piezoelectric layer and the number of layers may be selected according to the intended use of the stacked piezoelectric device.

[0086] In a further embodiment, the piezoelectric device may comprise, for example, a drive circuit, a current monitoring circuit, a switching device, as disclosed, for example, in DE 102015101817 A1.

[0087] The fields of application of the piezoelectric device according to the invention are not subject to any restrictions and include, in particular, ultrasonic cleaning, ultrasonic processing, sonar technology, sensor technology, actuator technology, material testing, medical diagnosis and treatment, the automotive industry, aerospace, mechanical engineering, construction equipment, ignition systems, consumer electronics and audio applications.

[0088] Example

[0089] according to Figure 1 The method steps schematically shown in FIG. 1 are based on the perovskite composition Ag x Bi y Pb z Fe v Ti w Various exemplary piezoelectric functional ceramics of O3 (where x+y+z=0.9 to 1.1 and v+w=0.9 to 1.1) were made into test sample disks with a size of 6.5 mm×1.0 mm (see Table 2). The compositions are shown in Table 1 below.

[0090] Table 1: Exemplary compositions and their Goldschmidt factors.

[0091]

[0092] To this end, the raw materials Ag2O, Bi2O3, PbTiO3, Fe2O3 and TiO2 were weighed, mixed in a 1-liter bucket and ground for 4 hours (in deionized water; 4:1 mixture; ZrO2 grinding beads). The diameter of the ground particles was determined using a laser particle size analyzer. 10 =0.7μm, d 50 =1.5μm and d 90=3.5 μm. The samples were dried at 120° C. for 24 hours and then granulated using a mesh screen (500 μm). For calcination, the substances were each filled into an Al2O3 crucible and calcined in air in a resistance-heated furnace (200° C. for 60 minutes, 750° C. for 600 minutes, 950° C. for 180 minutes). The cooled samples were subjected to phase analysis by XRD, which allowed the presence of non-perovskite heterogeneous phases to be excluded. The calcined material was finely ground in a 1 liter bucket for 4 hours (d 10 =0.7μm, d 50 =1.5μm and d 90 =3.5 μm), dried at 120°C for 24 hours, sieved using a mesh (500 μm), and then granulated after adding 0.8 wt% of PAF (bulk density d 堆积 =2.5g / cm 3 ). Uniaxial dry pressing (pressing force 34kN) was used to obtain a 12mm diameter, 30mm height, and a bulk density of 5.2g / cm 3 The compacts were then sintered, ground into a round shape (d = 6.5 mm), and sawn into disks (d = 6.5 mm, h = 1.0 mm) according to the conditions listed in Table 1. For ceramic analysis, the sintered disks were ground, polished, and heat treated at 950 ° C for 2 hours in a resistance-heated furnace. The grain size in the ceramic structure was imaged by optical microscopy and quantified by cross-sectional line measurements and Saltykov analysis (see Table 2).

[0093] Table 2: Sintering conditions and specific grain size parameters of sintered ceramic-on-ceramic structures.

[0094]

[0095]

[0096] Figure 2a and 2b Examples of ceramic images of sintered samples B and C are shown.

[0097] The samples were then coated with silver paste and fired at 850°C and subjected to a polarization step (6.5 kV / mm for 15 min at 25°C in oil) after cooling to room temperature.

[0098] The piezoelectric and dielectric properties of the polarized material (cylinder with dimensions d=6.5 mm, h=7.0 mm) were examined using an impedance analyzer. The results are summarized in Table 3.

[0099] Table 3: Dielectric and piezoelectric properties of exemplary compositions.

[0100]

[0101] f s : resonant frequency; tanδ: dielectric loss factor; ε: dielectric constant, k eff : Effective coupling factor

[0102] The data show that the material according to the invention has an advantageous high piezoelectric constant d 33 (above 70pC / N) and high Curie temperature T c (550℃ to 650℃).

[0103] In order to estimate the maximum use temperature, the thermal aging stability of the exemplary ceramics was tested in a further series of tests. For this purpose, the samples were aged at different temperature levels, starting from 300° C. for 20 h each, and the piezoelectric constant d of the samples (cylinders with dimensions d=6.5 mm and h=7.0 mm) was determined. 33 The aging temperature T is at least 60% of the initial value (measured at room temperature) A The results of these aging tests are shown in Table 4.

[0104] Table 4: According to the piezoelectric coefficient d 33 Determine the aging temperature (at least 60 hours heat treatment).

[0105]

[0106] The obtained data indicate that the perovskite compounds according to the present invention are capable of providing functional ceramics with excellent piezoelectric and dielectric properties at high temperatures.

Claims

1. A compound having a perovskite structure, characterized in that It has a basic composition of Ag x Bi y M z Fe v N w O3, wherein x+y+z=0.9 to 1.1 and v+w=0.9 to 1.1, wherein M is selected from Pb and / or Ba, and wherein N is selected from Ti and / or Zr.

2. The compound having a perovskite structure according to claim 1, wherein x, y, z, v and w satisfy: 0.01≤x≤0.20 0.50≤y≤0.80 0.05≤z≤0.50 0.50≤v≤0.70 0.30≤w≤0.50。 3. The compound having a perovskite structure according to any one of claims 1 or 2, wherein x, y, z, v and w satisfy: 0.02≤x≤0.14 0.56≤y≤0.76 0.10≤z≤0.42 0.54≤v≤0.62 0.38≤w≤0.46。 4. The compound having a perovskite structure according to any one of claims 1 to 3, wherein the compound has a perovskite structure tolerance factor according to Goldschmidt t in the range of 0.820 to 0.880, preferably in the range of 0.840 to 0.

860.

5. The compound having a perovskite structure according to any one of claims 1 to 4, wherein Ag + and Bi 3+ Occupies position A in the underlying perovskite base structure ABO3.

6. The compound having a perovskite structure according to any one of claims 1 to 5, wherein Fe 3+ and Ti 4+ Occupies position B in the underlying perovskite base structure ABO3.

7. A material having a piezoelectric function, characterized in that: The material includes a perovskite material containing the compound according to any one of claims 1 to 6.

8. The material of claim 7, wherein the material consists of an X-ray image-pure perovskite material, free of non-perovskite foreign phases detectable in X-ray images.

9. The material according to any one of claims 7 or 8, wherein the perovskite material does not contain a compound having the formula (Bi a K 1-a )TiO3, a perovskite phase wherein 0.4≤a≤0.6, and wherein the perovskite material preferably does not contain potassium ions.

10. The material of any one of claims 7 to 9, wherein the perovskite material is doped with manganese (Mn).

11. The material according to any one of claims 7 to 10, wherein the material has a piezoelectric function at an operating temperature of at most 500°C, and preferably has a piezoelectric constant d at an operating temperature of at most 500°C. 33 (In the case of electric field and length change along the polarization axis direction (longitudinal effect)) is greater than 50 pC / N, and more preferably greater than 60 pC / N.

12. A method for producing a material having piezoelectric functionality according to any one of claims 7 to 11, comprising: (1) mixing a raw material combination comprising Ag, Bi, Pb and / or Ba, Fe, Ti and / or Zr, and O, and optionally grinding the raw material combination; (2) heat treating the mixed and optionally ground raw material combination to provide a raw material having a composition of Ag x Bi y M z Fe v N w Perovskite material of O3, wherein x+y+z=0.9 to 1.1 and v+w=0.9 to 1.1, wherein M is selected from Pb and / or Ba, and wherein N is selected from Ti and / or Zr.

13. The process according to claim 12, wherein an aqueous medium and preferably water is used as mixing and / or grinding medium in step (1).

14. The method according to any one of claims 12 or 13, wherein the raw material combination comprises Bi2O3, Fe2O3, TiO2 and / or ZrO2, and PbTiO3 and / or BaTiO3, and one or more compounds selected from Ag2O, AgF, AgCl, AgBr, AgI, AgNO3, AgCNO, AgN3, Ag2S and AgOH, preferably one or more compounds selected from Ag2O, AgCl, AgBr, AgI, AgCNO, AgN3, Ag2S and AgOH, and particularly preferably Ag2O.

15. A piezoelectric device, preferably comprising a piezoelectric ceramic body having at least two electrodes, the piezoelectric device comprising the compound having a perovskite structure according to any one of claims 1 to 6 or the material having a piezoelectric function according to any one of claims 7 to 11.

Citation Information

Patent Citations

  • PIEZOELECTRIC DEVICE, PIEZOACTOR, HARD DISK DRIVE AND INKJET PRINTER

    DE102015101817A1

  • PIEZOELECTRIC COMPOSITION AND PIEZOELECTRIC COMPONENT

    DE102019135245B9

  • Manufacturing method for monolithic multi-layer piezoceramic actuator with microfaults provided in actuator joints parallel to inner electrodes

    DE10234787C1

  • Production of lead-free piezoceramics in aqueous surroundings

    EP3331840A1

  • ceramic

    US20130207020A1